2008
DOI: 10.1021/op600280g
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Effective Palladium Removal Process for VEGF Oncology Candidate AG13736 and a Simple, Efficient Screening Technique for Scavenger Reagent Identification

Abstract: AG13736 (Axitinib), an inhibitor of vascular endothelial growth factor (VEGF) under investigation as an oncology drug, is currently manufactured via a three-step process that utilizes two palladium-mediated cross-couplings. Historically, removal of residual heavy metals from the active pharmaceutical ingredient has been a persistent issue. The development of a much improved process for palladium removal and a useful screening technique developed to rapidly identify the most efficient reagents for this purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 9 publications
(8 reference statements)
1
51
0
Order By: Relevance
“…A slightly higher leaching under H 2 -lean conditions is well in line with the literature observations of a decreased leaching in the presence of hydrogen [61]. However, it should be noted that in both of the cases, leaching was orders of magnitude below the acceptable level that is an order of 1000 ppb [62]. A possible reason for such a low difference in leaching levels is likely that even under H 2 -lean condition, the major part of the tube length is still operating in hydrogen excess.…”
Section: Effect Of Liquid Flow Ratessupporting
confidence: 92%
“…A slightly higher leaching under H 2 -lean conditions is well in line with the literature observations of a decreased leaching in the presence of hydrogen [61]. However, it should be noted that in both of the cases, leaching was orders of magnitude below the acceptable level that is an order of 1000 ppb [62]. A possible reason for such a low difference in leaching levels is likely that even under H 2 -lean condition, the major part of the tube length is still operating in hydrogen excess.…”
Section: Effect Of Liquid Flow Ratessupporting
confidence: 92%
“…In most cases where the use of heterogeneous catalysts for C À C coupling reactions has been reported, [11] a careful study of the reaction mechanism revealed that, under the conditions employed, the supported species acted as "Trojan horses", [12,13] servng as reservoirs of the "soluble" active species generated in the course of the reaction. [14] This very often leads to a contamination of the final products with metals, [15] which is a key factor for the pharmaceutical industry. [16] Furthermore, the reaction requires the use of a base to neutralize the acid formed giving rise to the formation of salts that complicate the downstream processing and the scaleup.…”
Section: Introductionmentioning
confidence: 99%
“…If not removed, these residues can causet he decomposition or isomerization of the product over time or negatively affect the yield of subsequent steps of the synthesis. Additionally,t hey preclude the use of such products in the synthesis of active pharmaceutical ingredients (API), [4][5][6][7][8][9][10] which are subjectt os trict legal limits on heavy-metal contamination (less than 10 ppm). [11] Thanks to the discoveryo fw ell-defined ruthenium catalysts Ru1-Ru6 (Figure 1), [12][13][14][15][16][17] olefin metathesis (OM) became av ery useful tool in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant product 4b contained 40 ppm of ruthenium (Table 1, entry 5). Scavengers I-III gave much better results (Table 1, entries [7][8][9][10][11][12][13][14][15][16][17][18][19]. The use of II (4.4 equiv) reduced the residual ruthenium content by two orders of magnitudew ith respect to the control experiment, down to 1.6 ppm ( Table 1, entry 12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation